1972
DOI: 10.1073/pnas.69.11.3341
|View full text |Cite
|
Sign up to set email alerts
|

A Pressor Substance in the Cerebrospinal Fluid of Normotensive and Hypertensive Patients

Abstract: A pressor polypeptide was isolated from the cerebrospinal fluid of normotensive and hypertensive patients. Pharmacologically it behaves like angiotensin I. A very significant correlation (r = 0.83, P < 0.001) was found between the concentration of this polypeptide and the blood pressure of essential hypertensive patients.Early theories about the pathogenesis of essential hypertensive disease claimed that neural mechanisms were involved. The classical experiments by Goldblatt and the discovery of the renin-angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Although CSF levels were high, confirming previous reports, 5 the levels of CSF angiotensinogen did not correlate with brain levels. These findings support our earlier suggestion that the CSF is a sink for angiotensinogen 43 and indicate that CSF values may not provide an accurate reflection of the regulation of local brain angiotensinogen levels.…”
Section: Discussionsupporting
confidence: 89%
“…Although CSF levels were high, confirming previous reports, 5 the levels of CSF angiotensinogen did not correlate with brain levels. These findings support our earlier suggestion that the CSF is a sink for angiotensinogen 43 and indicate that CSF values may not provide an accurate reflection of the regulation of local brain angiotensinogen levels.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, ANG II content in outflowing aCSF perfusate was found to be increased in conscious restrained rats [13] and native CSF of dogs ap pears to contain higher ANG levels when collected immedi ately after induction of anesthesia [20], The elevated ANG II levels measured in the CSF of the New Zealand strain [62] of spontaneously hypertensive rats (SHR) seem to contribute to the hypertension, since the blood pressure decreased after the intraventricular injection of the ANG II receptor antagonist saralasin [13]. It has also been reported that ANG-like material was increased in CSF of hyperten sive patients [8]. The blood pressure lowering effect of intra ventricular saralasin was confirmed in the Japanese strain [34] of stroke-prone SHR even when animals were nephrectomized 15-20 h previously [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, the significance of such entry, if it does occur, is questionable, and the evidence for it is indirect. 27,30 'Values separated by a dash represent ranges. I = immunoassay; B = bioassay.…”
Section: The Brain Renin-angiotensin Systemmentioning
confidence: 99%